2022
DOI: 10.1073/pnas.2117064119
|View full text |Cite
|
Sign up to set email alerts
|

Multiple lines of evidence of early goose domestication in a 7,000-y-old rice cultivation village in the lower Yangtze River, China

Abstract: Significance We studied goose bones from Tianluoshan—a 7,000-y-old rice cultivation village in the lower Yangtze River valley, China—using histological, geochemical, biochemical, and morphological approaches. Our analyses reveal an early stage of goose domestication at Tianluoshan. The goose population seemed to have been maintained for several generations without the introduction of individuals from other populations and might have been fed cultivated paddy rice. These findings indicate that goose d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“… (A) Synthesis of the transformation process of subsistence strategies and landscape changes in the SHB. At each cultural stage, the most representative features of subsistence strategy were marked in the figure (data collected from Zong et al, 2007 ; Archaeological Research Center of Peking University and Zhejiang Provincial Institute of Cultural Relics and Archaeology, 2011 ; Jiang, 2014 ; Zhejiang Provincial Institute of Cultural Relics and Archaeology, 2016 , 2021 ; Zuo et al, 2017 ; Zhang et al, 2020 ; Eda et al, 2022 ; Official account of Qianjiang Evening News, 2022 ). (B) Trends of the proportions of domesticated-type bulliform phytoliths from rice ( Ma et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“… (A) Synthesis of the transformation process of subsistence strategies and landscape changes in the SHB. At each cultural stage, the most representative features of subsistence strategy were marked in the figure (data collected from Zong et al, 2007 ; Archaeological Research Center of Peking University and Zhejiang Provincial Institute of Cultural Relics and Archaeology, 2011 ; Jiang, 2014 ; Zhejiang Provincial Institute of Cultural Relics and Archaeology, 2016 , 2021 ; Zuo et al, 2017 ; Zhang et al, 2020 ; Eda et al, 2022 ; Official account of Qianjiang Evening News, 2022 ). (B) Trends of the proportions of domesticated-type bulliform phytoliths from rice ( Ma et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The domestic goose is one of the most economically important agricultural animals, as it can provide nutritious meat, eggs, and fatty liver. The geese bones from Tianluoshan in the lower Yangtze River showed that Chinese geese were domesticated more than 7,000 years ago 1 . Under the influences of diverse economic cultures and geographical structures, 30 Chinese indigenous geese breeds with different phenotypic features and production performance have gradually been formed 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Domestic chickens were originated from red jungle fowl subspecies ~ 8000 years ago [ 56 , 57 ], and ducks in East Asia were domesticated in China before 2200 BP [ 8 ]. However, recently published archaeological research has found goose bone fossils in a 7000-year-old cultivation village in the lower Yangtze River, China [ 14 ]. Unfortunately, the study did not extract ancient DNA for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The domestication of geese in China can be traced back to the Neolithic period (5000 BC), as evidenced by a goose-shaped artifact from that period [ 13 ]. In 2022, goose bone fossils were found in a 7000-year-old rice-cultivation village in the lower Yangtze River, China [ 14 ]. After a long period of domestication, China has had abundant domestic-goose breeding resources.…”
Section: Introductionmentioning
confidence: 99%